Future research avenues for the study of fibropapillomatosis in sea turtles - Dupont, Sophie M.; Bustamante, Paco; Duffy, David J.; Fort, Jérôme; Le Loc’h, Guillaume; Lelong, Pierre; Chevallier, Damien; Giraudeau, Mathieu (Frontiers in Ecology and Evolution, 2024)
Fibropapillomatosis (FP) is a debilitating tumoral disease affecting sea turtles worldwide. While mainly afflicting immature individuals and potentially altering vital functions, the precise impact of this panzootic on turtle health and survival remains unclear. Moreover, the etiological factors implicated in the FP emergence, development and transmission are not yet definitively identified. Among them, an infection by a spreading herpesvirus and the contamination by pollutants (either organic pollutants and trace elements) are suspected. Here, we provide an overview of discoveries, knowledge and propose hypotheses related to FP within five key FP research areas, i.e., virology studies, transmission studies, contamination studies, host genomic studies, and veterinary treatment assays. Moreover, we recommend urgent research avenues to develop at the interface of virology, epidemiology, ecotoxicology, oncology, physiology, immunology, cellular and evolutionary biology, in order to characterize the dynamics of FP and to predict its consequences on sea turtle populations. Importantly, extending the implementation and development of strong collaborations between rehabilitation centers, field biologists and research laboratories at large geographical scale is required to rapidly increase our knowledge on FP and work towards its effective management.